Association analyses identify 31 new risk loci for colorectal cancer susceptibility - Law, Philip J.; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Nature Communications, 2019)
In colorectal cancer (CRC), finding loci associated with risk may give insight into disease aetiology. Here, the authors report a genome-wide association analysis in Europeans of 34,627 CRC cases and 71,379 controls, and find 31 new risk loci and 17 new risk SNPs at previously reported loci.
Gesehen am 29.05.2019